1998
DOI: 10.1095/biolreprod58.3.739
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-Associated Gene Expression in the Corpus Luteum of the Rat1

Abstract: The involution of the corpus luteum (CL) at parturition is an example of physiological apoptosis, a complex process involving massive vascular regression while luteal cells undergo apoptosis. In the present study, changes in gene expression associated with physiological apoptosis were examined. Three genes isolated in our laboratory because of their association with apoptotic processes in the ovary, mammary gland, and prostate served as the focus of our investigation: Y81, Gas-1, and the gene IAP encoding inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 28 publications
4
57
0
Order By: Relevance
“…We have previously shown that DDC-4/sFRP-4 was upregulated in various tissues undergoing physiological apoptosis. 3,4,45 The new data show that DDC-4/sFRP-4 expression is a stimulus rather than a consequence of the apoptotic program in the mammary gland. Since DDC-4 is an sFRP and thus thought to sequester Wnt ligands, we propose a role for DDC-4/sFRP-4 in abrogating a Wnt-regulated survival pathway, the latter possibly signaling via PKB/Akt.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…We have previously shown that DDC-4/sFRP-4 was upregulated in various tissues undergoing physiological apoptosis. 3,4,45 The new data show that DDC-4/sFRP-4 expression is a stimulus rather than a consequence of the apoptotic program in the mammary gland. Since DDC-4 is an sFRP and thus thought to sequester Wnt ligands, we propose a role for DDC-4/sFRP-4 in abrogating a Wnt-regulated survival pathway, the latter possibly signaling via PKB/Akt.…”
Section: Discussionmentioning
confidence: 82%
“…45,53 The rabbit affinity purified anti-DDC-4 serum was used at a dilution of 1:100 on tissue sections after microwave treatment in 50 mM sodium citrate for 5 min at reduced energy (maximum temperature, 901C). For BrdU labeling, females were injected I.P.…”
Section: Isolation Of Rna and Northern Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of pregnancy in the rat, the most evident sign of luteal regression is the abrupt decrease in P 4 secretion by the luteal cells, which is followed by their apoptotic death (Guo et al 1998). The factors responsible for initiating and mediating luteal regression are very complex.…”
Section: Introductionmentioning
confidence: 99%
“…The ro le of sFRP downre gu la ti on in bre ast can cers has been furt her con fir med by a number of aut hors. [30][31][32][33] In this study, we in ves ti ga ted; 1-Ex pres si on le vels of β-ca te nin, cyclin D1, sFRP1 and sFRP2 in the bre ast can cer tis su e, 2-The inf lu en ce of me no pa u sal sta tus, es tro gen re cep tor, pro ges te rone re cep tor, c-erbB2, p53 po si ti vity, lymph no de in vol ve ment and cli ni cal TNM sta ge on the expres si on of β-ca te nin, cyclin D1, sFRP1 and sFRP2, 3-The ef fect of the eva lu a ted pa ra me ters on β-ca te nin, cli ni copat ho lo gi cal prog nos tic pa rame ters inc lu ding his to lo gi cal gra de, lymph no de in vol ve ment and TNM sta ge.…”
mentioning
confidence: 99%